2014
DOI: 10.1007/s10343-014-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Standorteigenschaften und Anbaumanagement erklären regionale Unterschiede im Kohlherniebefall in Deutschland

Abstract: Befallsintensitäten aufwiesen. In unserer Untersuchung beeinflussten die Bodenart, der Sandgehalt sowie der BodenpH-Wert das Vorkommen von P. brassicae. Bodenarten mit Sandgehalten von 30 bis 35 % und niedrigen BodenpH-Werten von unter 5,6 korrelierten auf den untersuchten Praxisschlägen mit hohen Befallsintensitäten. Schlüsselwörter Regionales Auftreten · Einflussfaktoren · Brassica napus · WinterrapsAbstract In the years 2013 and 2014 the presence and the infestation level of Plasmodiophora brassicae in six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…This observation is in agreement with a recent study by Strehlow et al . (). In their study, 66% of 237 farm fields investigated using a bioassay of soil samples showed clubroot infestation, with a mean disease severity of 34%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This observation is in agreement with a recent study by Strehlow et al . (). In their study, 66% of 237 farm fields investigated using a bioassay of soil samples showed clubroot infestation, with a mean disease severity of 34%.…”
Section: Discussionmentioning
confidence: 97%
“…However, the populations of the pathogen used in the present study were not single‐spore isolates and this may have resulted in the differences observed. Previously confirmed Mendel resistance‐breaking isolates originated from the Lower Saxony, Saxony, Hesse, Bavaria, West German Emsland and Westphalia regions (Strehlow et al ., ). The present investigation also found virulent isolates in Baden Würtemberg, Rhineland‐Palatinate and Thuringia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clubroot has been reported in more than 60 countries or regions around the world, and, in recent years, the disease has become increasingly serious. In Europe, North America, East Asia, and other regions, clubroot has become a major threat (Dixon, 2009; Chittem et al, 2014; Galdames et al, 2014; Strehlow et al, 2014; Wallenhammar et al, 2014; Strelkov et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Clubroot of oilseed rape ( Brassica napus ; OSR), caused by an obligate biotroph pathogen Plasmodiophora brassicae , is a destructive disease and an emerging threat to German OSR production (Lüders et al ., ; Diederichsen et al ., ; Strehlow et al ., ; Zamani‐Noor, ). Differences in clubroot disease incidence and severity were observed among German Federal States due to the differences in the pathotype complex, OSR genotypes, regional weather conditions and agricultural practices (Strehlow et al ., ; Zamani‐Noor, ).…”
Section: Introductionmentioning
confidence: 99%